Changes in muscle biochemical composition of Labeo rohita (Ham.) in relation to season - Shekhar, Chandra (Indian Journal of Fisheries, 2011)
Seasonal changes in the muscle biochemical composition of Labeo rohita (Ham.) were examined. Protein, carbohydrate and total ash content were higher in summer season, whereas moisture content was low. Fat and cholesterol content were also higher in summer in comparison to winter. Amino acids (lysine, methionine and tryptophan) content were higher in summer season. The highest value of calcium and phosphorus were also observed in summer.